Analysis of the Bacillus cereus SpoIIS antitoxin-toxin system reveals its three-component nature - Melnicakova, Jana; Becarova, Zuzana; Makroczyova, Jana; Barak, Imrich (Frontiers in Microbiology, 2015)
Programmed cell death in bacteria is generally associated with two¬ component toxin antitoxin systems. The SpoIIS toxin-antitoxin system, consisting of a membrane bound SpoIISA toxin and a small, cytosolic antitoxin SpoIISB, was originally identified in Bacillus subtilis. In this work we describe the Bacillus cereus SpoIIS system which is a three-component system, harbouring an additional gene spoIISC. Its protein product serves as an antitoxin, and similarly as SpoIISB, is able to bind SpoIISA and abolish its toxic effect. Our results indicate that SpoIISC seems to be present not only in B. cereus but also in other Bacilli containing a SpoIIS toxin antitoxin system. In addition, we show that B. cereus SpoIISA can form higher oligomers and we discuss the possible role of this multimerization for the protein’s toxic function.